Metrical Characteristics of the Childfit Battery of Tests for Measuring Motor Achievements in Preschool Children - Petrić, Vilko (Revija za elementarno izobraževanje, 2019)
The aim of this research is to evaluate the Childfit Battery of Tests measuring early and preschool children’s motor achievements. The test items that determine the content validity were systematically analysed, the test – retest procedure applied and the Pearson’s correlation coefficient between two intervals of measurement calculated, all with the aim of determining the test’s reliability. All parts of the object of measurement are proportionally present, and the test items are relevant for the same. The correlation of results in two measurement intervals is statistically significant and ranges from 0.91 to 0.94. The Childfit tests satisfy the validity and reliability criteria and are applicable for the measurement of early and preschool children’s motor achievements.
Keywords: childfit tests; motor achievements; validity; reliability; early and preschool age